The Prevalence of Concurrent Pulmonary and Extrapulmonary Tuberculosis in Uganda: a retrospective - Kyagulanyi, Eddy; Mirembe, Joy; Nantaayi, Brandy; Nalukenge, Sonita; Mukasa, David; Tamale, Jaffar; Oriekot, Anthony; Kamya, Moses R.; Baluku, Joseph Baruch (Therapeutic Advances in Infectious Disease, 2022)
Concurrent pulmonary tuberculosis (PTB) and extrapulmonary tuberculosis (EPTB) is associated with poor treatment outcomes yet its epidemiology in Uganda is unknown. The purpose of this study was to determine the prevalence, associated factors, and treatment outcomes of concurrent PTB and EPTB among patients at a national tuberculosis (TB) treatment center located at Mulago National Referral Hospital in Kampala, Uganda. We conducted a retrospective review of charts for people with TB who were enrolled in care between January 2015 and December 2019. Eligible charts were for people with pulmonary bacteriologically confirmed TB enrolled into care in the period under study. Concurrent PTB and EPTB was defined as PTB and bacteriological, histopathological, and/or radiological features of TB at another noncontiguous sites. Overall, 400 patient charts were eligible, of whom 240 (60.0%) were aged 15–34years and 205 (51.3%) were female. The prevalence of concurrent PTB and EPTB was 8.5% (34/400) [95% confidence interval (CI): 6.0–11.7%]. People with concurrent PTB and EPTB were more likely to have at least one comorbidity (82.4% versus 37.2%, p<0.001), of which HIV was the most frequent. Furthermore, people with concurrent PTB and EPTB were more likely to have empyema (15% versus 2.6%, p=0.028) but less likely to have bronchopneumonic opacification (0.0% versus 15.3%, p=0.043) on chest x-ray imaging. People with concurrent PTB and EPTB had higher mortality (26.5% versus 6.37%) and a lower cure rate (41.2% versus 64.8%), p=0.002. Our findings highlight the need for early detection of TB before dissemination particularly among people who use alcohol and people with HIV.
Keywords: Tuberculosis; PTB; Disseminated; EPTB; outcomes; HIV